PENGGUNAAN BAHASA GAUL PADA MEDIA SOSIAL TIKTOK: The Use of Slang on Tiktok Social Media - Fadila, Nur; Anshari; Hajrah (Journal of Applied Linguistics and Literature, 2025)
This study aims to describe the forms of slang and the impact of slang usage on the social media platform TikTok. This study uses a descriptive qualitative approach, with data sources from TikTok app posts. The data in this study consists of phrases, sentences, and clauses in TikTok social media user posts. The data collection techniques in this study are observation, reading, and screen capture. The data analysis techniques in this study are data collection, data reduction, presentation, and conclusion drawing. Data validity was examined using source triangulation. The results of the study show that there are forms of slang on TikTok social media, namely abbreviations (acronyms and abbreviations), reversals, foreign languages, and puns. The impact of the use of slang on TikTok social media is the displacement of proper and correct Indonesian, difficulty in understanding communication, but it can increase creativity and innovation in the development of the Indonesian language.